Tongue acupuncture for the treatment of post-stroke dysphagia: a meta-analysis of randomized controlled trials - Li, Li; Xu, Fei; Yang, Shengping; Kuang, Peng; Ding, Haoying; Huang, Mei; Guo, Chunyan; Yuan, Zishui; Xiao, Xiao; Wang, Zuhong; Zhang, Pengyue (Frontiers in Neuroscience, 2023)
Objectives: Stroke is the most common neurological cause of dysphagia. The swallowing process is controlled by the network of the cerebral cortex, subcortical area and brainstem structure. The disruption of the swallowing network after stroke leads to dysphagia. Swallowing muscle mainly includes laryngeal muscle (suprahyoid muscle and thyrohyoid muscle) and infrahyoid muscle. These muscles experience kinematic effects and muscle strength weakens, resulting in reduced movement in the swallowing process. Acupuncture can change the excitability of cerebral cortical nerve cells, promote the recovery of neurological function, and enhance the neuromuscular excitability, ultimately improve the control of swallowing-related nerves and muscles, and promotes swallowing functional recovery. In this meta-analysis we systematically evaluate the clinical efficacy of acupuncture in the treatment of post-stroke dysphagia. Methods: Randomized controlled trials of acupuncture therapy for poststroke dysphagia were searched and selected from seven electronic databases (PubMed, CBM, Cochrane, Embase, CNKI, VIP, and Wanfang). The Cochrane collaboration tool was used to conduct methodological quality assessment. RevMan v5.4 software was utilized to perform data analysis. Results: A total of 25 studies with 2106 patients were included. Meta-analysis showed that WST score[MD=-056, 95% CI (-1.23,0.12),Z=1.62,P<0.00001)],SSA score [MD=-1.65, 95% CI (-2.02, -1.28) , Z=8.77, P<0.00001)] , VFSS score [MD＝1.83, 95%CI（1.17，2.49,Z=5.45, P＜0.00001] , sEMG score [MD＝1.83,96%CI（1.04, 3.47, Z=3.64, P＜0.00001], All of these results suggested that the treatment group (acupuncture, tongue acupuncture and acupuncture combined with other therapies) was superior to the control group in reducing WST scores and SSA scores. Using VFSS score and sEMG score as observation indexes, the curative effect was higher than that in the control group. The clinical efficacy of acupuncture combined with other therapies [MD＝1.17, 95%CI（1.12, 1.21）, Z=7.53, P＜0.00001], was better than that of the control group. Conclusion: The meta-analysis indicated that the total effective rate of patients with dysphagia after stroke in the treatment group (acupuncture, tongue acupuncture and acupuncture combined with other therapy) is higher than that in the control group.